Asymmetric severity of diabetic retinopathy in Waardenburg syndrome: response to authors - Gupta A (Dove Medical Press, 2012)
Aditi Gupta, Rajiv Raman, Tarun SharmaShri Bhagwan Mahavir Department of Vitreoretinal Services, Sankara Nethralaya, Chennai, Tamil Nadu, IndiaWe read with great interest the recent article by Kashima et al,1 in which the authors report a case of asymmetric severity of diabetic retinopathy in Waardenburg syndrome. We want to highlight some concerns regarding this report. Previous reports have described many systemic and local factors associated with the development of asymmetric diabetic retinopathy.2,3 These include myopia ≥5 D, anisometropia >1 D, amblyopia, unilateral elevated intraocular pressure, complete posterior vitreous detachment, unilateral carotid artery stenosis, ocular ischemic syndrome, and chorioretinal scarring.2,3 In any suspected case of asymmetric diabetic retinopathy, it is prudent to rule out the abovementioned factors first. In the present case, although the authors clearly mention the absence of internal carotid and ophthalmic artery obstruction on magnetic resonance angiography, it would have been more informative if the authors had also provided the refractive error, intraocular pressure, and posterior vitreous detachment status of both the eyes.Likewise, it would have been useful to note the arm-retina time and retinal arteriovenous filling time in both the eyes on fundus fluorescein angiography, which is usually used to diagnose ocular ischemic syndrome by monitoring extension of the retinal circulation time, including time of blood circulation from the arm to the retina and the retinal arteriovenous filling time.4,5 The mere absence of internal carotid obstruction on magnetic resonance angiography cannot rule out the presence of ocular ischemic syndrome because, rarely, ocular ischemic syndrome can also occur secondary to other causes, such as arteritis.6,7 Comparing the arm-retina time and retinal arteriovenous filling time on fundus fluorescein angiography in both the eyes would be more helpful to rule out ocular ischemic syndrome.